1973
DOI: 10.1103/physrevlett.30.1279
|View full text |Cite
|
Sign up to set email alerts
|

Observation ofZ=70QuasiatomicKX Rays from 30- and 60-MeVBr35

Abstract: A K-x-ray band up to the united-atom limit for Z-lO has been observed in 30-and 60-MeV Br + Br collisions. This band can be assigned unambiguously to transitions between molecular orbitals. With a KBr target, yields at the two energies are (for Ey.^22 keV) 2 X 10"^ and 10"^ photons/projectile, respectively, or 10"'^ photon s/be am ii vacancy, nearly independent of beam energy. Much reduced yields are found for Ti, Fe, and Zr targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1974
1974
1985
1985

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…For this reason, attention was directed toward high-Z w ion-atom collisions, where the energy levels are less sensitive to the charge state of the ions, and the MO x rays could conceivably be calculated with one-electron MO's. Meyerhof et aL (1973) reported the observation of Is a MO x rays in Br + Br collisions whose end points matched that expected for the UA (Z=70). This work was challenged by Davis and Greenberg (1974), most seriously on the grounds that the end-point energy is not a sufficient clue to the identity of the continuum x rays: first, because high-energy nucleus-nucleus bremsstrahlung (NNB) and x-ray continuum backgrounds (see Sec.…”
Section: Historical Overviewsupporting
confidence: 55%
“…For this reason, attention was directed toward high-Z w ion-atom collisions, where the energy levels are less sensitive to the charge state of the ions, and the MO x rays could conceivably be calculated with one-electron MO's. Meyerhof et aL (1973) reported the observation of Is a MO x rays in Br + Br collisions whose end points matched that expected for the UA (Z=70). This work was challenged by Davis and Greenberg (1974), most seriously on the grounds that the end-point energy is not a sufficient clue to the identity of the continuum x rays: first, because high-energy nucleus-nucleus bremsstrahlung (NNB) and x-ray continuum backgrounds (see Sec.…”
Section: Historical Overviewsupporting
confidence: 55%
“…However, it is possible to make comparisons with experimental dat& for the lighter elements. Scofield has compared the total K emission rates with experimental quantities for 10 elements between Z = 16 and 79, and the agreement appeared to be within the experimental uncertainties.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…These authors showed that the anisotropies reach a maximum at an X-ray energy which can only be explained by transitions into the 2p a-minimum. Evidence for the quasimolecular nature of this continuum also is given by the fact that the Dopplershift-determined following the method of Meyerhof et al [1][2][3][4][5]-is due to the center-of-mass-motion of the colliding system. In our measurements described below we determined the energies of the peak centroids of the 2p a-aniso- tropies in five symmetric systems in order to investigate the Z-dependence of the effect.…”
Section: Introductionmentioning
confidence: 98%
“…By quasimolecular radiation we understand radiation produced by transitions between transiently formed inner shell orbitals around the two charge centers. The X-ray continuum is composed of two parts: a high energy-continuum-extending up to energies above the united atom K-limit-which can be attributed to MO-lsa-radiation [1] and a more steeply decreasing low energy part which does not fit into the quasiatomic picture since it reaches energies which are much higher than the united atom L-limit. This radiation has been interpreted as being due the transitions into the minimum of the 2pa-orbital [2].…”
Section: Introductionmentioning
confidence: 99%